Tween‐80 and impurity induce anaphylactoid reaction in zebrafish. Issue 3 (27th October 2014) - Yang, Rui; Lao, Qiao‐Cong; Yu, Hang‐Ping; Zhang, Yong; Liu, Hong‐Cui; Luan, Lin; Sun, Hui‐Min; Li, Chun‐Qi
Abstract A number of recent reports suspected that Tween‐80 in injectable medicines, including traditional Chinese medicine injections could cause life‐threatening anaphylactoid reaction, but no sound conclusion was drawn. A drug‐induced anaphylactoid reaction is hard to be assayed in vitro and in conventional animal models. In this study, we developed a microplate‐based quantitative in vivo zebrafish assay for assessing anaphylactoid reaction and live whole zebrafish mast cell tryptase activity was quantitatively measured at a wavelength of 405 nm using N‐benzoyl‐dl‐arginine p‐nitroanilide as a substrate. We assessed 10 batches of Tween‐80 solutions from various national and international suppliers and three Tween‐80 impurities (ethylene glycol, 2‐chloroethanol and hydrogen peroxide) in this model and found that three batches of Tween‐80 (nos 2, 20080709 and 20080616) and one Tween‐80 impurity, hydrogen peroxide (H2O2), induced anaphylactoid reactions in zebrafish. Furthermore, we found that H2O2 residue and peroxide value were much higher in Tween‐80 samples 2, 20080709 and 20080616. These findings suggest that H2O2 residue in combination with oxidized fatty acid residues (measured as peroxide value) or more likely the oxidized fatty acid residues in Tween‐80 samples, but not Tween‐80 itself, may induce anaphylactoid reaction. High‐throughput zebrafish tryptase assay developed in this report could be used for assessing safety of Tween‐80‐containing injectable medicines and potentially for screening novel mast cell‐modulating drugs. Copyright © 2014 John Wiley & Sons, Ltd.